Ultrastable single-component organic solar cells: the next frontier towards industrial viability - He, Yakun; Brabec, Christoph; Heumüller, Thomas; Wortmann, Jonas; Hanisch, Benedict; Aubele, Anna; Li, Ning; Feng, Guitao; Jiang, Xudong; Li, Weiwei; Bäuerle, Peter; Lucas, Sebastian (Proceedings of International Conference on Hybrid and Organic Photovoltaics (HOPV22), 2022)
Power conversion efficiencies (PCEs) of bulk heterojunction (BHJ) organic solar cells (OSCs) continue increasing towards the 20% milestone mainly due to the emerging non-fullerene acceptors (NFAs). While significant efforts have been devoted to efficiency analysis, important factors for industrial application are mostly neglected, such as photostability and the cost potential. Single-component organic solar cells (SCOSCs) employing materials with donor and acceptor moieties chemically bonded within one molecule or polymer, successfully overcome the immiscibility between donor and acceptor as well as the resultant self-aggregation under external stress [1]. To inspire a broader interest, in this work, the industrial figure of merit (i-FOM) of OSCs are calculated and analyzed, which includes PCE, photostability, and synthetic complexity (SC) index [2]. Based on the notable advantages of SCOSCs over the correspondent BHJ OSCs, especially the enhanced stability and simplified film processing, we systematically compare the i-FOM values of BHJ OSCs and the corresponding SCOSCs. SCMs exhibit overall much higher i-FOM values compared with the BHJ OSCs, and the highest value reaches 0.3, which is comparable with (or higher than) the ones of high-efficiency BHJ OSCs. With the increase of efficiency, SCOSCs possess the further potential to a higher i-FOM value. Among all factors, the synthetic complexity of SCOSCs is slightly higher than that of the corresponding BHJ OSCs due to the extra synthetic step for connecting donor and acceptor moieties. Nevertheless, the covalent bonding structure of SCMs helps overcome the immiscibility between D and A for proper nanophase separation and consequently a decent PCE, in comparison with the large-scale phase separation for the corresponding BHJ systems. More importantly, the higher i-FOM of SCOSCs is mostly ascribed to the substantially enhanced stability compared with BHJ [3]. SCOSCs based on dyad 1 exhibit surprisingly high photostability under concentrated light (7.5 suns and 30 suns), corresponding to an almost unchanged device stability up to ten thousand hours under 1-sun illumination. For realizing industrial application, SCOSCs have to give a high efficiency comparable to the current high-efficiency BHJ OSCs, while BHJ should be developed in the direction of less complicated synthesis. With joint efforts of researchers from multidiscipline, SCOSCs will see continuing progress in efficiency, reaching an i-FOM value enough for industrial application. <br